PERAN DINAS SOSIAL DALAM MEMBENTUK LIFE SKILL ANAK JALANAN DI KOTA SERANG - Lady Diana; Dinar Sugiana Fitrayadi; Ria Yuni Lestari (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2020)
The purpose of this study: 1) to determine the Role of the Social Service in Shaping the Life Skill of Street Children in Serang City 2) to find out the Activities carried out by the Social Service in Shaping the Life Skill of street children in the City of Serang 3) to find out the Obstacles experienced by the Social Service in forming Life Skill of street children in Serang City. The method used: descriptive method with a qualitative approach. The instruments used: observation, interviews, and documentation. Research subjects: Serang City Social Service and Street Children in Serang City. The results of this study indicate that the Role of Social Services in Shaping the Life Skill of Street Children in Serang City through self-knowledge, rational thinking skills, social skills, academic skills, and vocational skills provided by social services in training program activities aimed at street children have the skills or abilities, able, and skilled to maintain the survival and development in the future. Activities undertaken by the Social Service in Forming Life Skills of street children: hindering activities and leadership training activities. Barriers experienced by the Social Service in forming Life Skills of street children: internal and external barriers which include internal obstacles in the submission of programs and target participants, external barriers include barriers to screening / blocking street children, it is difficult to change the mindset of street children and parents who are blocking follow-up process in handling street children.